2015
DOI: 10.1007/s10439-015-1314-7
|View full text |Cite
|
Sign up to set email alerts
|

Controlled and Extended Release of a Model Protein from a Microsphere-Hydrogel Drug Delivery System

Abstract: In extended ocular drug delivery applications, it is necessary to exert control over the release characteristics of the drug. Design considerations must be made to limit the initial burst (IB) and ensure complete release of drug from the drug delivery system (DDS). In this study, ovalbumin was used as a model protein to explore the effects on release of polymer formulation and fabrication technique in poly(lactic-co-glycolic acid) (PLGA) microspheres. Furthermore, the effect on release of suspending these micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 23 publications
2
56
0
Order By: Relevance
“…In recent years, various ophthalmic drug-delivery systems have been developed for ocular carriers, including liposomes (LPs), [6][7][8] nanoparticles, 9,10 microspheres, 11,12 nanostructured lipid carriers, 13,14 in situ gels, 15,16 and contact lenses. 17 Among these, LPs have proved to be a promising formulation for ocular drug transport in the last decade, because they include enclosed vesicles and bilayer structures.…”
Section: Huang Et Almentioning
confidence: 99%
“…In recent years, various ophthalmic drug-delivery systems have been developed for ocular carriers, including liposomes (LPs), [6][7][8] nanoparticles, 9,10 microspheres, 11,12 nanostructured lipid carriers, 13,14 in situ gels, 15,16 and contact lenses. 17 Among these, LPs have proved to be a promising formulation for ocular drug transport in the last decade, because they include enclosed vesicles and bilayer structures.…”
Section: Huang Et Almentioning
confidence: 99%
“…18,21,22 In addition, sustained release of drugs with tailored characteristics can be achieved by encapsulating drugs within PLGA microspheres. 17 Moreover, our previous studies have demonstrated controlled release of bioactive anti-VEGF therapeutics from PLGA microspheres for approximately 200 days. 17,20 To further investigate the potential clinical usage of anti-VEGF-loaded DDS, in vivo studies of the safety and biocompatibility of the device is required, preferentially in the eyes of an animal model that has similar eye size and retinal structure as a human.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Therefore we developed a DDS consisting of biodegradable poly lactic-co-glycolic acid (PLGA) microspheres suspended within a thermo-responsive, injectable hydrogel to address this clinical requirement. 17,18 Thermo-responsive hydrogel has demonstrated great promise in drug delivery owing to their ability to change physical state rapidly and is reversible. Below the transition temperature (∼32°C) the hydrogel is swollen in liquid-like form, and above the transition temperature the hydrogel collapses to solidified form.…”
Section: Introductionmentioning
confidence: 99%
“…They are particularly important in cancer therapy where the therapeutic index of the drug is often quite small and the stability of biologic agents is limited. 24, 40 In situ forming implants (ISFI) used for local drug delivery directly into the tissue of interest (e.g. a tumor) are an attractive alternative route to oral and intravenous administration.…”
Section: Introductionmentioning
confidence: 99%